2020
DOI: 10.1093/esr/jcaa044
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dimensions of Unemployment and Relationship Happiness in the United Kingdom

Abstract: Here we study how unemployment is related to partner relationship happiness in the United Kingdom. We investigate multiple dimensions of unemployment—current unemployment, changes in unemployment, duration of unemployment, and past unemployment—each of which provides unique insights into how economic uncertainty can strain relationships. Not including these aspects potentially leads to an underestimation of the long-term effect of unemployment and times when couples are especially affected. Using British longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although the interaction terms in the main models were not significant, the couple sample findings suggest that men may have appreciated the break from work more than women, which then transferred over to their own evaluation of their relationships. Previous studies have found that in the UK couples still adhere to traditional gender expectations for men to work; for example, women whose husbands became unemployed experienced a decline in relationship quality, while men whose wives become unemployed do not (Blom & Perelli‐Harris, 2020). The furlough scheme, however, does not seem to be equivalent to unemployment, instead socially permitting men to take paid leave, and sanctioned as a way to avoid job loss.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the interaction terms in the main models were not significant, the couple sample findings suggest that men may have appreciated the break from work more than women, which then transferred over to their own evaluation of their relationships. Previous studies have found that in the UK couples still adhere to traditional gender expectations for men to work; for example, women whose husbands became unemployed experienced a decline in relationship quality, while men whose wives become unemployed do not (Blom & Perelli‐Harris, 2020). The furlough scheme, however, does not seem to be equivalent to unemployment, instead socially permitting men to take paid leave, and sanctioned as a way to avoid job loss.…”
Section: Discussionmentioning
confidence: 99%
“…For example in Germany, falling below the poverty line decreased relationship satisfaction for women, but not men (Hardie et al, 2014). In the UK, women became unhappy with their relationship when their husbands lost their jobs, but women's own unemployment did not result in a decline in relationship happiness for either partner (Blom & Perelli-Harris, 2020). Men's employment seems to be particularly important when there is a societal expectation that men adopt an economic provider role (Hardie et al, 2014).…”
Section: Gender Differences In the Association Between Economic Uncer...mentioning
confidence: 99%
See 3 more Smart Citations